Development of Digital Economy in the Energy Industry-specific Modernization - Kapitonov, Ivan A.; Filosofova, Tatiana G.; Korolev, Vitaly G. (International Journal of Energy Economics and Policy, 2019)
Digitalization of economy defines the extent of possibility in the use of the single information field that could have defined the possibilities for the forecast of the enterprise's activities. The novelty of the study is in the fact that it implements the aspects of the formation of a single forecasting structure for the consumption of the energy sector's production components within a single energy information system. The paper deals with the digitalization of the energy branch based on the approach to the forecast of possible consumption of products. The practical significance of the study is defined by the fact that there is a possibility of formation of a single component on the modernization of the enterprises if they participate in applying the results of the digitalization of economy in the national production system. The implementation of the approach is illustrated by the example of the Republic of Kazakhstan. Keywords: energy, industry, modeling, forecasting, economy. JEL Classifications: O13, Q47 DOI: https://doi.org/10.32479/ijeep.8013